The Moderating Effect of Technostress on The Relationship between Personality Traits and Employee Turnover Intentions - Ghosn, Myriam (2022)
Organizations all around the world face turnover, which is caused by multiple reasons, and one of them could be personality traits of the employees. The purpose of this study is to examine the nature of the relationship between personality traits and employee turnover intentions, while studying the moderating effect of technostress on this relationship. Technostress constitutes an important variable since recently, most employees are frequently using information and communication technologies (ICTs) at their work, which is causing them technostress. The nature of this research is quantitative, in which the relationship between the chosen variables has been measured using an online questionnaire, sent to respondents working in the Middle East. The data was later on analyzed through SPSS statistical software. The study finds that there is a negative relationship between personality traits and employee turnover intentions, and that technostress moderates, partially moderates some traits, and do not moderate others.